Princess of the Midnight Ball - George, Jessica Day, 1976- (Princess of the Midnight Ball, 2009)
A retelling of the tale of twelve princesses who wear out their shoes dancing every night, and of Galen, a former soldier now working in the king's gardens, who follows them in hopes of breaking the curse.